Active surveillance of carbapenem-resistant Gram-negative healthcare-associated infections in a low-middle-income country city - Viviane Maria de Carvalho Hessel Dias; Daniela Maria Waszak da Silva; Marion Burger; Alcides Augusto Souto de Oliveira; Patrícia de Jesus Capelo; Fabio Augusto da Rocha Specian; Marianna Cavina de Figueiredo; Felipe Francisco Tuon; Cristina Pellegrino Baena (Brazilian Journal of Infectious Diseases, 2021)
Background: Carbapenem-resistance in healthcare-associated infections (HCAIs) is of great concern, and it is urgent to improve surveillance. We aimed to describe and analyze HCAIs trends on Gram-negative antimicrobial susceptibility in a city from a developing country, following the implementation of an active surveillance program. Methods: This is an aggregated study describing data from 24 hospitals with intensive care units, including a trend analysis by Joinpoint regression between January 2012 and December 2017. Results: There were 23,578 pathogens in 39,832 HCAIs, from which 16,225 were Gram-negatives (68.8%). Carbapenem susceptibility was lowest in A. baumannii (15.4–25.9%), K. pneumoniae (51.0–55.9%), and P. aeruginosa (64.9–84.1%) and highest in E. coli (96.5–99.2%). Only K. pneumoniae showed a significant Joinpoint at 95% confidence interval: −10.71% (−18.02; −2.75) from 2012 to 2014, p = 0.02, and 6.54% (−2.00; 15.83) from 2015 to 2017, p = 0.12, which was most influenced by urinary tract infections: −9.98% (−16.02; −3.48) from 2012 to 2014, p = 0.01, and 9.66% (−1.75; 22.39) from 2015 to 2017, p = 0.09. Conclusion: Although we found a significant change toward an improvement in carbapenem susceptibility in K. pneumoniae, resistance is high for most pathogens. These data should encourage health institutions to improve their prevention and control strategies.